Distrust of Institutions. A problem in John Searle’s social ontology - González Fernández, Rodrigo Alfonso (Revista de Filosofía, 2025)
This article deals with how distrust of institutions is problematic for Searle’s social ontology. The first section analyzes collective intentionality and its relationship with cooperation. The second section examines how institutional trust and distrust are neglected in Searle’s social ontology. The third section explains why conflict of interests causes interpersonal and institutional distrust. The fourth section identifies the critical mass of intentional agents as the source of institutional crisis. Finally, the fifth section postulates a role for distrust in the serlean social reality.
Keywords: collective intentionality; collective recognition; trust; distrust; conflict of interests; crisis of institutions